Current Limitations of Surgical Robotics in Reconstructive Plastic Microsurgery - Tan, Youri P. A.; Liverneaux, Philippe; Wong, Jason K. F. (Frontiers in Surgery, 2018)
Surgical robots have the potential to provide surgeons with increased capabilities, such as removing physiologic tremor, scaling motion and increasing manual dexterity. Several surgical specialties have subsequently integrated robotic surgery into common clinical practice. Plastic and reconstructive microsurgical procedures have not yet benefitted significantly from technical developments observed within the last two decades. Several studies have successfully demonstrated the feasibility of utilising surgical robots in plastic surgery procedures, yet limited work has been done to identify and analyse current barriers that have prevented wide scale adaptation of surgical robots for microsurgery. Therefore, a systematic review using PubMed, MEDLINE, Embase and Web of Science databases was performed, in order to evaluate current state of surgical robotics within the field of reconstructive microsurgery and their limitations. Despite the theoretical potential of surgical robots, current commercially available robotic systems are sub-optimal for plastic or reconstructive microsurgery. Absence of bespoke microsurgical instruments, increases in operating time and high costs associated with robotic-assisted provide a barrier to utilising such systems effectively for reconstructive microsurgery. Consequently, surgical robots provide currently little overall advantage over conventional microsurgery. Nevertheless, if current barriers can be addressed and systems are specifically designed for microsurgery, surgical robots may have the potential of meaningful impact on clinical outcome within reconstructive microsurgery.